CURRICULUM IN EARLY CHILDHOOD EDUCATION FABRIC - Cristiane Elvira de Assis Oliveira (Editora da Universidade de Santa Cruz do Sul, 2014)
This text aims to show what the kindergarten teachers, a school full-time education, a mining town, narrated about temporalities woven into the curriculum with a focus on the organization of curricular time. Temporalities refer to multiple ways of dealing with time, or in my experience and time. The teachers devised the curriculum in the school routine, embracing it as something that is woven with the facts and the natural beauty of everyday actions. By understanding the multiple temporalities at school, you can rethink the logic of curriculum organization and diversify the curriculum, researching other ways of enabling children to learn, to question the logic of prescriptive curriculum and consider the curriculum as a cultural artifact, as something that creates, becomes a creative way and that is woven every day by teachers with children in various everyday practices in / of / with the school.